2019
DOI: 10.1177/000313481908501136
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiation Therapy is Associated with Adverse Outcomes in Patients Undergoing Pancreaticoduodenectomy for Pancreatic Cancer

Abstract: The use of neoadjuvant chemoradiation therapy in patients with pancreatic adenocarcinoma is emerg-ing as an acceptable therapy option. The effects of neoadjuvant therapy on 30 days’ outcomes in patients with pancreatic cancer are not well defined in the literature. NSQIP (2009–2012) was used. Only patients with a diagnosis of pancreatic cancer and those who underwent a Whipple were included in the analysis. Patient who underwent neoadjuvant chemoradiation therapy were compared with those who did not receive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…19 A few studies argued against this, 20,21 but most found no statistically significant difference. [22][23][24][25][26][27] Survival data were calculated using the declining exponential approximation of life expectancy method. The average patient was assumed to be a 65-year-old male with a predicted life expectancy of 18.09 years.…”
Section: Data Selectionmentioning
confidence: 99%
“…19 A few studies argued against this, 20,21 but most found no statistically significant difference. [22][23][24][25][26][27] Survival data were calculated using the declining exponential approximation of life expectancy method. The average patient was assumed to be a 65-year-old male with a predicted life expectancy of 18.09 years.…”
Section: Data Selectionmentioning
confidence: 99%
“…The American Joint Committee on Cancer (AJCC) staging system is currently the tool widely used by oncologists for predicting the prognosis of PaC patients (10). However, the AJCC staging system does not consider specific individuals, including the tumor differentiation grade (11), therapy method (12,13), and number of regional LNs examined. In reality, various factors can influence the cancer course and prognosis of PaC patients, and refining and establishing a new model for specific individuals (i.e., PLN-PaCs) are thus important.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an increase in adverse events occurs with the combination of multiple chemotherapy regimens or chemotherapy and radiotherapy. 8,9 Recently, intensive research has been performed in the field of targeted therapy and immunotherapy, 10,11 although changes in patient survival have been marginal at best, and their prognosis remains relatively dismal. 11 Thus, identifying biomarkers for early detection and targets for the treatment of patients with PDAC is a pressing challenge.…”
mentioning
confidence: 99%